Enhancing urban centers: connecting grey with green in Kansas City's downtown loop - Fuemmeler, Chadd Randall (Kansas State University, 2011)
In the late 1800s George Kessler and the Board of Parks and Boulevard Commissioners (BPBC) developed a Parks and Boulevard system for Kansas City, MO laying the foundation for the city to grow. Development of the system is the result of the combination of Kessler’s ideology, as well as his planning and design practices. The parks and boulevard system established a framework giving due weight to existing conditions, adapting itself to topography, avoiding forced routes and forced construction. This framework based itself around the value of beauty, the city’s duty, the effect of parkways and boulevards on real-estate values, and the experience of other cities. Today, auto-centric sprawl has revealed its limitations, bringing focus back to the neglected urban fabric. The current urban fabric is dominated with automotive infrastructure responding only to the pedestrian where convenient or required. Results of this trend in development are concrete jungles. Unfortunately, the city character developed by the expanded parks and open space systems has been or is in danger of being lost. Opportunities for redevelopment are rising as these expansive urban infrastructures are reaching the end of their designed life cycle. As people begin to repopulate urban areas, revitalization of the parks and green space is of high priority. Adapting George Kessler’s practices, principles, and ideals behind the Kansas City Parks and Boulevard System to contemporary practices, principles, and ideals in landscape architecture will allow a designer to enhance urban centers. Using my findings, I will develop a master plan for the Kansas City Downtown Loop. By enhancing sites with parks and plazas connected with pedestrian friendly greenways, the Downtown Loop will be a safer, more pleasant place for pedestrians and motorists alike.
Keywords: Urban center; Downtown; Connection; Kansas City; Area Planning and Development (0341); History (0578); Landscape Architecture (0390)